THE LINGUISTIC PROBLEMS OF STUDENTSâ COMPETENCE IN WRITING BUSINESS LETTERS - Pratiwi, Yuni Eka; Rukmini, Dwi; Faridi, Abdurrahman (Language Circle: Journal of Language and Literature, 2017)
A good writing not only restates the message or idea using sentences or expressions that are grammatically correct, but also has to organize idea or message in a form which is easy to understand. The aims of this research were 1) to explain the organizations of business letters produced by the twelfth grade students of the office management program of Ky Ageng Giri Mranggen, Demak Vocational High School; 2)Â  to explain the contents of business letters produced by the students; 3) to explain the grammars of business letters produced by the students; 4) to explain the vocabularies of business letters produced by the students; 5) to explain the mechanics of business letters produced by the students; 6) to explain the writing competence of business letters produced by the students. A qualitative case study was used in this research.The findings derived from studentsâ work. They showed that in the organization of business letters, they can organize the part of letter completely, from the letter head, date, inside address, salutation, give state the purpose, explain the information, conclude and thank to the reader, complementary close, and additional information if necessary. For the content, they got difficulty in what the idea they should write. In grammar, they didnât know the verb form of simple past, confused to use the personal pronoun in English, the structure of sentence, differentiatethe auxiliaries, the articles and using degree of comparison. For vocabulary, they got difficulties in using and choosing vocabulary.In the mechanic, they made mistakes in using spelling, punctuation, and capitalization. The findings of the studentsâ competencies in writing business letters, there were 75.00% students whowere competent in writing business letters, almost of them mastered the organization, mechanic, and the content of letters. 25.00% students who had no-competent, they still got difficulty in using grammar and choose the vocabulary.Â  Almost half students in the class passed the exam. It can be concluded that the twelfth grade students of the office management program of Ky Ageng Giri Mranggen, Demak Vocational High School are competent in writing business letters.